Examination papers from the University of Cambridge Local Examinations Syndicate - Carne, Paul (Cambridge, UK, 1998)
This collection of four complte practice tests comprises past papers from the Cambridge First Certificate in English examination set in 1996 and 1997 by the University of Cambridge Local Examinations Syndicate.
Keywords: English language,English language; Textbooks for foreign speakers,Examinations, questions, etc